2013
DOI: 10.5604/15093492.1084355
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Parameters of Spinal Curves in the Sagittal Plane Measured by Photogrammetry and Inclinometry

Abstract: STRESZC ZE NIE Wstęp. Me to da fo to gra me trycz na oraz po mia ry in kli no me trycz ne są czę sto sto so wa ny mi spo so ba mi oce ny przed nio -tyl nych krzy wizn krę go słu pa. Me to dy te wy ko rzy sty wa ne są do pro wa dze nia ba dań kli nicz nych, jak i przesie wo wych. Ce lem pra cy jest po rów na nie pa ra me trów opi su ją cych krzy wi zny przed nio -tyl ne krę go słu pa w po miarze me to dą fo to gra me trycz ną i in kli no me trycz ną.Ma te riał i me to dy. Do ba dań włą czo no 341 dzie ci (169 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
(2 reference statements)
0
6
1
1
Order By: Relevance
“…The presented findings are not consistent with the research results reported by Walicka-Cupryś et al who assessed spinal curvatures with liquid-based inclinometer and photogrammetric technique [12,23]. These authors did not find the two methods to be compatible.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…The presented findings are not consistent with the research results reported by Walicka-Cupryś et al who assessed spinal curvatures with liquid-based inclinometer and photogrammetric technique [12,23]. These authors did not find the two methods to be compatible.…”
Section: Discussioncontrasting
confidence: 98%
“…The results reported by various researchers are difficult to compare due to the fact that different methods and measuring tools are applied; therefore, it is necessary to continue studies designed to compare results obtained with specific methods. Among the specialist publications we can encounter articles discussing concurrent validity of various techniques designed for assessing body posture [12,[23][24][25]], yet no research has previously been reported to compare the methods based on photogrammetry and gravitational inclinometer, which has been done in the present study. The two methods were used in assessing the same subjects, which made it possible to verify the assumption regarding the concurrent validity of these measurements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pod sta wa fi zycz na tych zja wisk no si w opty ce nazwę zja wi ska Mo ire'a. Ba da nie wy ko na no we dług za le ceń po da nych przez pro du cen ta [8,9]. Na pod stawie uzy ska nych fo to gra mów do ko na no ana li zy posta wy cia ła w opar ciu o ozna czo ne wcze śniej punk ty an tro po me trycz ne i wy zna czo no na stę pu ją ce pa rame try opi su ją ce po sta wę cia ła:…”
Section: Methodsunclassified